EDUCATIONAL PSYCHOLOGY: A TOOL FOR LANGUAGE RESEARCH - Rahmat, Noor Hanim (PEOPLE: International Journal of Social Sciences, 2018)
Many researchers who studied language learning in the classroom have used theories of educational psychology as their foundation of knowledge. Understanding the theories of educational psychology and how they can be useful in classroom learning can help researchers answer the “why” in research. Some language researchers choose to study language teaching methodology, others prefer studies that look into the behavior of language learners. There are also some language studies that looked into the influence of the environment on language teaching and learning. This paper reports findings of past studies in the language classroom that used educational psychology as basis for understanding behaviour in teaching and learning.